2019
DOI: 10.1073/pnas.1813909116
|View full text |Cite
|
Sign up to set email alerts
|

A glycan shield on chimpanzee CD4 protects against infection by primate lentiviruses (HIV/SIV)

Abstract: Pandemic HIV-1 (group M) emerged following the cross-species transmission of a simian immunodeficiency virus from chimpanzees (SIVcpz) to humans. Primate lentiviruses (HIV/SIV) require the T cell receptor CD4 to enter into target cells. By surveying the sequence and function of CD4 in 50 chimpanzee individuals, we find that all chimpanzee CD4 alleles encode a fixed, chimpanzeespecific substitution (34T) that creates a glycosylation site on the virus binding surface of the CD4 receptor. Additionally, a single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 75 publications
(85 reference statements)
2
13
0
Order By: Relevance
“…2 A ). This PNGS, which has been experimentally confirmed to be glycosylated ( 61 ), appears to occupy a similar structural position as the chimpanzee glycan at position 66, which is known to interfere with SIV Env binding ( 55 ). To examine whether N15 has a protective effect, we changed the asparagine at position 15 in one representative gorilla CD4 allele (AHSM) to a threonine, which is present in all other African primates.…”
Section: Resultsmentioning
confidence: 95%
“…2 A ). This PNGS, which has been experimentally confirmed to be glycosylated ( 61 ), appears to occupy a similar structural position as the chimpanzee glycan at position 66, which is known to interfere with SIV Env binding ( 55 ). To examine whether N15 has a protective effect, we changed the asparagine at position 15 in one representative gorilla CD4 allele (AHSM) to a threonine, which is present in all other African primates.…”
Section: Resultsmentioning
confidence: 95%
“…An increasing number of studies have suggested that coevolution is driven by specific interactions between high levels of virus sequence divergence and polymorphic host receptors (40,41,(43)(44)(45)(46). The first example was observed for the avian leucosis virus infection, in which receptor polymorphism in chicken could alter the sensitivity to virus entry (44).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of pathogen sequence divergence can further accelerate with increased polymorphism of host receptors (Gupta et al, 2009;Meyerson and Sawyer, 2011;Warren et al, 2019), allowing pathogens to infect and adapt to another host more effectively (Daugherty and Malik, 2012). For instance, a recent study that analysed ACE2 receptors in Chinese Horseshoe bats (Rhinolophus sinicus) found multiple such highly polymorphic sites in the receptor regions which interacts with the spike proteins of SARSr-CoV, coronavirus isolated from the same species of bats (Guo et al, 2020).…”
Section: B Complex Interplay With Life-historymentioning
confidence: 99%